2019
DOI: 10.29252/jmp.4.72.81
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Essential Oil Content and Composition of Peppermint (Mentha piperita L.) in Responses to Nitrogen Application

Abstract: Background: Nitrogen is the most important nutrient requirement for plants. Nitrogen supplying affected the leaf area, carbon fixation, glandular trichomes formation, ATP and NADPH content which resulted to the terpenoids biosynthesis enhancement and essential oils accumulation. Objective: This study was aimed to evaluate changes of essential oil content and components by use different levels of Urea fertilizer and its relation with the antioxidant status of peppermint. Method: The two field experiments were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…The higher concentration of the CA enzyme would naturally be responsible for the improved activity of the enzyme. The results corroborate with the findings of [ 24 ] on Brassica juncea L. [ 25 , 26 ], on Mentha spicata L. and on Mentha piperita L. [ 27 ]. The foliar spray of N improved leaf N, P and K contents compared to the water spray treatment ( Figure 4 A–C).…”
Section: Discussionsupporting
confidence: 91%
“…The higher concentration of the CA enzyme would naturally be responsible for the improved activity of the enzyme. The results corroborate with the findings of [ 24 ] on Brassica juncea L. [ 25 , 26 ], on Mentha spicata L. and on Mentha piperita L. [ 27 ]. The foliar spray of N improved leaf N, P and K contents compared to the water spray treatment ( Figure 4 A–C).…”
Section: Discussionsupporting
confidence: 91%
“…The knowledge of trace element and heavy metals content in different chemical fertilizers is useful for estimation of the environmental potential risks resulting from high loading application of fertilizers 8 . In Table 7, the background mean content of trace elements and heavy metals in worldwide soils are presented 21 . Cumulative release of NO 3 − from slow release fertilizer at different concentrations during the time is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogen is a predominant element in chlorophyll structure. Increasing of NO 3 − dosage significantly affects the chlorophylls content 21 . Increasing of chlorophyll content caused to increase of leaf area due to increase of light adsorption 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sheykholeslami and Qasempour Almdari (2019) demonstrated that plants treated with 15 ton vermicompost ha −1 achieved the highest oil and biomass yield of peppermint. Seif Sahandi, Naghdibadi, Mehrafarin, Khalighi‐Sigaroodi, and Sharifi (2019) showed that 150 kg urea ha −1 resulted in higher antioxidant activity and changed most of the essential oil components except α‐terpineol, Z ‐β‐ocimene, 1,8‐cineole, limonene, myrcene and β‐pinene.…”
Section: Introductionmentioning
confidence: 99%